Creeping Through the Backdoor: Disruption in Medicine and Health - Shaw, Brendan; Chisholm, Orin (Frontiers in Pharmacology, 2020)
Can disruption happen when no one notices? Disruptive technologies and processes are fundamentally starting to up-end how medicines and health systems benefit patients but the question is whether health systems are ready for it. This paper will briefly review the business strategy and management literature on topics such as disruption and “black swan” theories of change, before turning to discuss some of the areas where change is affecting medicine and health care. Such areas include the emergence of cell and gene therapies, the economics of cures, digital technologies, mobile apps, social media, supply chain technologies such as drones and online distribution, universal health coverage and funding, and consumerisation of healthcare. The question to be asked is whether these sorts of changes are ‘disruptive’ or whether they were coming for a long time and it is just that health systems are slow to change. It could be argued that while perhaps unexpected by day-to-day practitioners in healthcare, in fact, many of the changes now starting to affect the health and medicines sector have been affecting other sectors such as technology, finance and communications for decades.